2021
DOI: 10.1186/s40163-021-00151-y
|View full text |Cite
|
Sign up to set email alerts
|

Crime and COVID-19: effect of changes in routine activities in Mexico City

Abstract: Background This study aimed to determine whether crime patterns in Mexico City changed due to the COVID-19 pandemic, and to test whether any changes observed were associated with the disruption of routine activities, as measured by changes in public transport passenger numbers. Method The first objective was assessed by comparing the observed incidence of crime after the COVID-19 pandemic was detected in the country with that expected based on ARIM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 33 publications
(37 reference statements)
1
36
0
2
Order By: Relevance
“…The decrease in shootings in Mexico City is consistent with the significant decrease in other types of crimes in the city during the pandemic, such as robberies of public transport [8], burglary and vehicle theft [9]. On an international level, this study coincides with the effects of the pandemic on crime: an overall decrease, as indicated by, for example, Shayegh and Malpede (2020) [23] in San Francisco, by Mohler et al (2020) [22] in Los Angeles and Indianapolis and by Campedelli (2020) [12] in Los Angeles.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The decrease in shootings in Mexico City is consistent with the significant decrease in other types of crimes in the city during the pandemic, such as robberies of public transport [8], burglary and vehicle theft [9]. On an international level, this study coincides with the effects of the pandemic on crime: an overall decrease, as indicated by, for example, Shayegh and Malpede (2020) [23] in San Francisco, by Mohler et al (2020) [22] in Los Angeles and Indianapolis and by Campedelli (2020) [12] in Los Angeles.…”
Section: Discussionsupporting
confidence: 63%
“…As far as we know, there are still no empirical studies in Latin America that look at shootings in the region during the COVID-19 pandemic. Despite this, there is a growing body of criminological research that studies the effects of the pandemic and the various restrictions imposed in the region on, for example, changes in crime pattens in Mexico City during the pandemic, such as crimes associated with public transport [8], burglary, vehicle theft [9], violence against women [37] and homicides [7]. There are also studies on problems related to prisons and the difficulties faced by various Latin American governments to resolve these [38,39].…”
Section: Crime During the Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…In the UK, Halford et al ( 2020 ) analysed changes in crime in Lancashire during March 2020, and noted that, by the week of March 23rd, there had been a large decrease in shoplifting, theft, theft from vehicles, domestic abuse, assault and residential and non-residential burglary. Changes in recorded crime were also found in Sweden (Gerell et al, 2020 ), Mexico (Estévez-Soto, 2021 ), China (Borrion et al, 2020 ) and Australia (Payne et al, 2021 ). Nivette et al ( 2021 ) recorded crime data from 27 cities across 23 countries and concluded that stay-at-home orders contributed to a considerable global drop in urban crime.…”
Section: Rapid Social Changes and Crime: The Covid-19 Casementioning
confidence: 86%
“…Although evidence on the mental health effects of the COVID-19 pandemic is continuously building, research examining the effects of the COVID-19 pandemic on calls for police service involving persons with perceived mental illness (PwPMI) is scant. 1 In fact, to-date, research examining the impacts of the pandemic on police-related activity has almost exclusively focused on crime (see e.g., Andresen & Hodgkinson, 2020 ; Ashby, 2020 ; Buil-Gil et al, 2020 ; Campedelli et al, 2020 ; Estévez-Soto, 2021 ; Felson et al, 2020 ; Gerell et al, 2020 ; Hodgkinson & Andresen, 2020 ; Langton et al, 2021 ; Payne et al, 2021 ; Piquero et al, 2021 ). While this area of inquiry is certainly important, crime only comprises approximately 20–30% of all police calls for service (Wuschke et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%